MEDICAL VERSUS SURGICAL MANAGEMENT OF OTITIS MEDIA WITH EFFUSION IN CHILDREN - Yousaf, Mohammad; Inayatullah, Inayatullah; Khan, Farida (Journal of Ayub Medical College Abbottabad, 2012)
Background: Otitis media with effusion (OME) is a leading cause of hearing difficulty in children. OME must be detected early and managed properly to prevent hearing and speech impairment in children. This study was aimed to compare results of medical and surgical treatments in terms of hearing improvement, recurrence of Middle Ear Effusion (MEE), time to offer surgical intervention. Methods: The study was conducted from June 2008 to December 2011. A performa was used to collect data. Every child having hearing difficulty was examined with pneumatic otoscope for fluid level and tympanic membrane mobility. These children were investigated with pure tone audiometry for level of hearing loss and tympanometry to confirm the middle ear effusion. X-Ray nasopharynx lateral view was taken to see if there were adenoids. All patients were treated conservatively in the first phase. Those not responding to conservative treatment were treated with myringotomy and adenoidectomy with or without ventilation tubes. Patients were followed-up for up to 36 months. Results: Middle ear effusion cleared in 80 (71.5%) out of 112 ears. No improvement was noted in 32 ears for 9 months. Resistant and recurrent cases were managed with adenoidectomy and myringotomy alone or with insertion of ventilation tubes (VT). Recurrence was noted more common with myringotomy alone than with ventilation tubes. Medical treatment failed in 32 ears. MEE recurred in 9 ears. VT was put in 41 ears. The hearing level improved with VT by 10-15 dB after first 3 months. Conclusion: All children with OME should be treated conservatively. It is cost effective and relieves MEE in about 70% of patients. The ears with OME that fails to resolve or recur should be managed with myringotomy and VT insertion or adenoidectomy. Keywords: otitis media with effusion, myringotomy, adenoids; rhinosinusitis, tympanometry